Vanda tricolor Lindl. conservation in Java, Indonesia: genetic and geographic structure and history - Gardiner, Lauren (Universidad de Costa Rica, 2015)
Vanda tricolor Lindl. is widespread in cultivation in South East Asia, being relatively easily cultivated in the garden, and is often seen growing floriferously on garden trees, fence posts and verandas. Whilst the species is widespread in cultivation in its native regions of Java and Bali, wild populations are small and highly fragmented. The author’s recent field trip to Java and Bali found few wild examples of the species, and the few plants found were in the most inaccessible trees, due to massive over-collection, often with no other V. tricolor plants to be found in the area.